Imminent threat of antibiotic resistance and the importance of diagnostic and antibiotic stewardship - Yusuf, Erlangga (Universa Medicina, 2017)
Antibiotic is one of the hallmarks of modern medicine. Antibiotics have saved many lives that was unthinkable prior to the discovery of antibiotic. Yet, antibiotic use is associated with the danger of resistance of bacteria. Resistance of bacteria to antibiotics means simply that antibiotics cannot be used to treat infection, that a simple skin and soft tissue infection may lead to death. Already in 1945, when Alexander Flemming received his Nobel Prize in 1945 for his part in the discovery of penicillin, he delivered a speech where he warned about this danger 1. In his speech, he mentioned the problem of underdosage of antibiotics. As the time passed by, we know that the problem is not only related to underdosage but also to other aspects of inappropriate use of antibiotics such as unnecessary use (for example when the infection is due to a virus), and extended duration of antibiotics 2.